Enhanced Biocontrol of Cucumber Fusarium Wilt by Combined Application of New Antagonistic Bacteria Bacillus amyloliquefaciens B2 and Phenolic Acid-Degrading Fungus Pleurotus ostreatus P5 - Wang, Hongwei; Cai, Xiao-Yu; Xu, Man; Tian, Feng (Frontiers in Microbiology, 2021)
Continuous monoculture of cucumber (Cucumis sativus L.) typically leads to frequent incidence of Fusarium wilt caused by Fusarium oxysporum f. sp. cucumerinum (FOC). As potent allelochemicals, phenolic acids are believed to be associated with soil-borne diseases. This study aimed to investigate the effect of single or co-inoculation of antagonistic bacteria B. amyloliquefaciens B2 and phenolic acid-degrading fungus Pleurotus ostreatus P5 on the suppression of cucumber Fusarium wilt. The strain B2 was identified as B. amyloliquefaciens based on biochemical, physiological, and 16S rDNA and gyrB gene sequence analyses. Strain B2 showed indole-3-acetic acid (IAA) and siderophore production, and phosphate solubilization in vitro assays. Scanning electron microscope (SEM) imaging showed the ability of strain B2 to adhere to the root surface of cucumber. P. ostreatus P5 could effectively degrade mixed phenolic acids as its sole source of carbon and energy for growth in liquid medium. In a pot experiment, four treatments were established: (1) CK: un-inoculated control, (2) B2: inoculation of strain B2, (3) P5: inoculation of strain P5, and (4) B2 + P5: co-inoculation of strain B2 and strain P5. At the end of the 60-day pot experiment, the B2, P5 and B2+P5 treatments significantly reduced disease incidence by 48.1%, 22.2% and 63.0%, respectively, compared to the CK treatment (p < 0.05). All three inoculation treatments significantly increased the growth of cucumber seedlings and suppressed the FOC population compared to the control (p < 0.05). HPLC analysis showed that total phenolic acids were decreased by 18.9%, 35.9% and 63.2% in the B2, P5 and B2+P5 treatments, respectively. The results from this study suggest that combined application of B. amyloliquefaciens B2 and P. ostreatus P5 could be a promising strategy for suppressing Fusarium wilt and improving plant growth of cucumber seedlings under continuous cropping conditions.